2018
DOI: 10.1165/rcmb.2016-0207oc
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus α-Toxin Induces Actin Filament Remodeling in Human Airway Epithelial Model Cells

Abstract: Exposure of cultured human airway epithelial model cells (16HBE14o-, S9) to Staphylococcus aureus α-toxin (hemolysin A, Hla) induces changes in cell morphology and cell layer integrity that are due to the inability of the cells to maintain stable cell-cell or focal contacts and to properly organize their actin cytoskeletons. The aim of this study was to identify Hla-activated signaling pathways involved in regulating the phosphorylation level of the actin-depolymerizing factor cofilin. We used recombinant wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 48 publications
4
25
0
3
Order By: Relevance
“…For example, the genes of the brown module are significantly associated with the biological pathways of Tuberculosis, Staphylococcus aureus infection, Leishmaniasis, Pertussis, and Legionellosis. All these pathways play critical roles in infections and remodeling in COPD (Carette et al 2018;Tsenova et al 2014;Ziesemer et al 2018;Sabulski et al 2017). In the brown module, eight hub DEGs including CYp27A1, GM2A, LGAL59, SPI1, PARVG, LOC644189, NLRC4, CD300LF are considered as the novel genes in the COPD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the genes of the brown module are significantly associated with the biological pathways of Tuberculosis, Staphylococcus aureus infection, Leishmaniasis, Pertussis, and Legionellosis. All these pathways play critical roles in infections and remodeling in COPD (Carette et al 2018;Tsenova et al 2014;Ziesemer et al 2018;Sabulski et al 2017). In the brown module, eight hub DEGs including CYp27A1, GM2A, LGAL59, SPI1, PARVG, LOC644189, NLRC4, CD300LF are considered as the novel genes in the COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Die Zellen zeigen auch eine Einschränkung der Fähigkeit, stabile fokale Kontakte zwischen Zellmembran und der extrazellulären Matrix zu bilden . Außerdem findet unter Hla‐Einwirkung eine massive Reorganisation des Aktin‐Zytoskeletts statt . Insgesamt führt dies zu deutlichen Änderungen der Zellform und der Ausbildung ▸ parazellulärer Lücken im Zellverband (Abbildung ).…”
Section: Biologische Bedeutung Der Porenbildungunclassified
“…Die durch Hla‐Einwirkung verursachte Lösung der Zell‐Zell‐Verbindungen (adherence junctions) erfolgt vermutlich durch eine Ca 2+ ‐vermittelte Aktivierung der Metalloprotease ADAM10 . Die Unfähigkeit, stabile ▸ fokale Kontakte zur Zellunterlage auszubilden und die Reorganisation des Aktin‐Zytoskeletts gehen auf die Hla‐vermittelte Intensivierung der Signaltransduktion durch die fokale Adhäsionskinase (FAK) sowie auf eine Hemmung der Aktivität der LIM‐Kinase zurück. In ruhenden Epithelzellen phosphoryliert die LIM‐Kinase den Aktin‐depolymerisierenden Faktor Cofilin und inaktiviert ihn dadurch, so dass die Aktin‐Stressfasern, die die Zellform stabilisieren, vor der abbauenden Aktivität des Cofilins geschützt sind.…”
Section: Biologische Bedeutung Der Porenbildungunclassified
See 1 more Smart Citation
“…That tissue remodeling and polyp formation may be favored in a dysbiotic microenvironment is inferred in a number of studies showing increased S. aureus colonization in the nasal cavities of patients with polyposis [ 164 ]. Recent work has shown that α -toxin, one of the major S. aureus toxins, can substantially contribute to airway remodeling via a combined effect on the epithelial cell cytoskeleton and endothelial TJ integrity, leading, respectively, to altered morphology and edema [ 165 , 166 ]. However, the main mechanism this far ascertained by which S. aureus may induce or favor nasal polyp formation is the production of such superantigens as staphylococcal enterotoxins (SAE) [ 7 , 167 ].…”
Section: Microbial Regulation Of Tissue Remodeling In Nasal Inflammentioning
confidence: 99%